Corporate Social Responsibility Law and the Prevention of MSMEs Bankruptcy in the Digital Era - Atika Sunarto; Nestiani Gulo; Putri Anggraini; Muhammad Ali Adnan (Universitas Islam Sultan Agung, 2026)
The digital era poses bankruptcy risks for MSMEs in Medan City due to low digital literacy, weak financial management, and limited market access. Corporate Social Responsibility (CSR) implemented by Bank Sumut Berkah plays a strategic role in preventing bankruptcy and enhancing the competitiveness of MSMEs. This study analyzes the implementation of CSR, the challenges encountered, and the impact of the program on business resilience in the digital era using a normative juridical method through literature review, policy document analysis, and semi-structured interviews. The findings indicate that the implementation of Corporate Social Responsibility by Bank Sumut Berkah significantly contributes to improving managerial capacity, financial literacy, business digitalization, and market access for Micro, Small, and Medium Enterprises. The program is able to reduce bankruptcy risk and strengthen business competitiveness in the digital era. The main challenges identified include limited understanding of digital technology, the short duration of mentoring, and uneven access to program information. Therefore, continuous assistance, broader program dissemination, and the establishment of business networks or communities are necessary to enhance program effectiveness.